2018
DOI: 10.1093/trstmh/try113
|View full text |Cite
|
Sign up to set email alerts
|

Tegumentary leishmaniasis and sand flies in a border area between Argentina and Bolivia

Abstract: Background: Some sand flies are of medical importance because they are vectors of Leishmania parasites that are responsible for leishmaniasis. The aim of this study was to make a retrospective epidemiological analysis of tegumentary leishmaniasis (TL), to identify Leishmania spp. from patient isolates and to describe the diversity of sand flies from a border area between Bolivia and Argentina.Methods: TL cases included in the study were diagnosed in an endemic area of the north of Argentina from 1985 to 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
3
0
2
Order By: Relevance
“…In the current study, we tested in greater depth its potential, extending the analysis to the species that were circulating in areas with ATL transmission. The species composition of sand flies reported in this work was concordant with past entomological captures performed in Orán department (Chanampa et al, 2018;Copa et al, 2018;Salomón et al, 2008Salomón et al, , 2004, in which Ny. neivai was also found as the most abundant species (Krolewiecki et al, 2013;Quintana et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, we tested in greater depth its potential, extending the analysis to the species that were circulating in areas with ATL transmission. The species composition of sand flies reported in this work was concordant with past entomological captures performed in Orán department (Chanampa et al, 2018;Copa et al, 2018;Salomón et al, 2008Salomón et al, , 2004, in which Ny. neivai was also found as the most abundant species (Krolewiecki et al, 2013;Quintana et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding Argentinian phlebotomine fauna, entomological studies showed the presence of 32 sand fly species distributed in 14 provinces (Szelag et al, 2016). The following species have been found in Salta province: Nyssomyia neivai, Migonemyia migonei, Psathyromyia bigeniculata, Psathyromyia punctigeniculata, Evandromyia cortelezzii, Evandromyia sallesi, Micropygomyia quinquefer, and Lutzomyia longipalpis (Barroso et al, 2007;Bravo et al, 2013;Chanampa et al, 2018;Copa et al, 2018;Quintana et al, 2010;Salomón et al, 2004). Most of these species are also present in the other provinces where Nyssomyia whitmani, Pintomyia pessoai, Pintomyia fischeri, and Brumptomyia spp.…”
Section: Introductionmentioning
confidence: 99%
“…En Argentina, así como en este estudio, se observó que el riesgo se asocia también con el trabajo rural o con la vegetación primaria 32 , el manejo de ganado, la caza, el dormir en espacios abiertos o permanecer en el exterior de la vivienda por más de diez horas, el bañarse en el río, así como la presencia de animales domésticos en el interior del domicilio, las vivienda sin cerramiento 32 - 34 , y la transmisión peridomiciliaria en viviendas hasta los 100 a 200 m de la vegetación primaria o secundaria, incluso en áreas urbanas 35 , 36 por el efecto de borde 37 .…”
Section: Discussionunclassified
“…En Bolivia, la especie más frecuentemente aislada es L. ( Viannia ) braziliensis. A la primera cepa aislada en Tarija, en un perro en el 2002, se añadieron tres otras cepas aisladas con los genotipos AB1 y AB2 35 . En el norte argentino se han confirmado casos poco frecuentes atribuidos a L. ( V. ) guyanensis, L. ( V. ) panamensis 29 y L. ( L. ) amazonensis 43 .…”
Section: Discussionunclassified
“…longipalpis in the northwestern Argentina-Bolivia border, in urban peridomestic environments in Salvador Mazza. The area had no records of this species in previous intensive sampling procedures, 4 , 5 , 10 until reports in 2013 in Tartagal, 55 km south from the Salvador Mazza-Bolivia border 6 . Second, the abundance of Lu.…”
mentioning
confidence: 99%